The legal methodology of late Nehardean sages in Sasanian Babyloni a - Cohen, Barak S. (The Brill Reference Library of Judaism, 2011)
This book consists of a systematic analysis of the halakhic/legal methodology of fourth and fifth century Nehardean amoraim in Babylonia (as well as their identity and dating). The book uncovers various distinct characteristics present in the halakhic decision making and source interpretation, and demonstrates how certain amoraim can be characterized as portraying consistent interpretive and legal approaches throughout talmudic literature. Understanding the methodological characteristics that distinguish some amoraim from other amoraim can aid the talmudic interpreter/scholar in clarifying the legal foundations of their rulings, the proofs that they bring within talmudic discourse, as well as their disputes and interpretations. This allows a better understanding of the development of Jewish Law and the legal system in talmudic Babylonia.